Ethnoveterinary Practices Of Some Plant Species By Ethnic People Of Parbat District, Nepal - Malla, Birendra; Chhetri, RB (Kathmandu University Journal of Science, Engineering and Technology, 2012)
In Parbat district, tribal communities rear livestock mostly cattle, buffalo, goats, sheep etc. Most of the time animal diseases are treated by the uses of local herbal medicines extracted from the plants. All together 21 plant species belonging to 19 families are being identified having used to treat different veterinary diseases like; injury, poisoning, foot and mouth, wounds, stomach disorder, antiworms and bone facture of animals. These ethnoveterinary plants species are normally collected from nearby forest or natural vegetation. Some of them like, Acorus calamus, Cuscuta reflexa, Schima wallichii, Fraxinus floribunda etc are even domesticated by them in nearby cropland therefore such plants are readily available at any time. DOI: http://dx.doi.org/10.3126/kuset.v8i1.6042 KUSET 2012; 8(1): 44-50